2022
DOI: 10.3389/fcimb.2022.815318
|View full text |Cite
|
Sign up to set email alerts
|

More Than Just a Periodontal Pathogen –the Research Progress on Fusobacterium nucleatum

Abstract: Fusobacterium nucleatum is a common oral opportunistic bacterium that can cause different infections. In recent years, studies have shown that F. nucleatum is enriched in lesions in periodontal diseases, halitosis, dental pulp infection, oral cancer, and systemic diseases. Hence, it can promote the development and/or progression of these conditions. The current study aimed to assess research progress in the epidemiological evidence, possible pathogenic mechanisms, and treatment methods of F. nucleatum in oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 166 publications
(182 reference statements)
1
44
0
3
Order By: Relevance
“…to the host tissue or that Fusobacterium spp. facilitated the co-adhesion of other bacteria, as reported for F. nucleatum in periodontal diseases 39 50 . F. nucleatum has tissue-adhesive and co-aggregating properties qua its virulence factors FadA Fap2, RadD, and FomA 3942 .…”
Section: Discussionsupporting
confidence: 59%
“…to the host tissue or that Fusobacterium spp. facilitated the co-adhesion of other bacteria, as reported for F. nucleatum in periodontal diseases 39 50 . F. nucleatum has tissue-adhesive and co-aggregating properties qua its virulence factors FadA Fap2, RadD, and FomA 3942 .…”
Section: Discussionsupporting
confidence: 59%
“…Thus, it can promote and accelerate the development of periodontitis. Moreover, Fusobacterium nucleatum can cause local halitosis and pulp infections and may systemically promote the development or progression of oral cancer and other extraoral diseases [ 62 ]. Kang et al [ 63 ] explored and identified three types of Weissella cibaria from human saliva, which produce hydrogen peroxides.…”
Section: Oral Microbiome In Periodontal Diseasesmentioning
confidence: 99%
“…Suzuki et al [ 64 ] showed that Lactobacillus saliva WB21 buccal tablets can specifically reduce the amount of F. nucleatum in patients with halitosis. This means that the use of W. cibaria and Lactobacillus saliva WB21 as probiotics can be a beneficial method of combating bad breath and controlling PD [ 62 , 64 ].…”
Section: Oral Microbiome In Periodontal Diseasesmentioning
confidence: 99%
“…The overlap of the unique members of oral microbes with other remote organs is consistent with previous clinical studies in which Fusobacterium nucleatum , a Gram-negative oral anaerobe, were clinically suspected to be a major risk factor in colorectal cancer [ 97 , 98 , 99 ], oral squamous cell carcinoma (OSCC) [ 100 ], and in preterm and term stillbirth [ 101 , 102 ]. Likewise, an infamous oral pathogenic bacterium, Porphyromonas gingivalis , is related to pancreatic cancer [ 103 ], colorectal cancer [ 104 , 105 , 106 ], liver health [ 107 ], rheumatoid arthritis [ 108 , 109 ], diabetes [ 110 , 111 , 112 ], OSCC [ 113 , 114 ], and neurodegenerative diseases [ 88 , 89 , 90 , 91 , 92 , 115 , 116 , 117 , 118 ]. In the case of atherosclerotic CVD, when the vascular tissues of the coronary and femoral arteries of the patients with CVD were examined, P. gingivalis was found in 42 out of 42 patients [ 119 ].…”
Section: Oral Pathogens and Systemic Diseasesmentioning
confidence: 99%